THE COSI, A DECADE DEVOTED TO THE EUROPEAN UNION INTERNAL SECURITY POLICY - SÁNCHEZ PELÁEZ, Leonardo (Journal of the Spanish Institute for Strategic Studies, 2022)
After several failed attempts, the signature of the Lisbon Treaty allowed the setting-up of the Standing Committee on Operational Cooperation on Internal Security (COSI). After an initial period of definition of the work procedures, the Committee has been strengthening and expanding its responsibilities, related to judicial and police cooperation, the implementation of the strategic directions of internal security, the fight against organized crime or the cooperation of the JHA agencies. Gradually, issues related to the fight against terrorism have also been added to its agenda, despite the reluctance of some Member States. Ten years after its creation, the COSI has demonstrated its ambition, adaptability and flexibility, abilities that have contributed to consolidating its position as a relevant actor in the field of internal security in the European Union.